Fungal inhibitory activity of sesquiterpenoids isolated from Laggera pterodonta - Liu, Yuxuan; Li, Jinliang; Wu, Guoxing; Wu, Xiaoyun; Zhao, Yuhan; Ding, Xiao; Qin, Xiaoping (Frontiers in Plant Science, 2025)
The phytochemical diversity of plants represents a valuable reservoir for novel agrochemical agents. Our preliminary investigations identified pronounced antifungal efficacy in Laggera pterodonta extracts, although this species remains critically understudied. Herein, six eudesmane-type sesquiterpenes (1–6) were isolated from L. pterodonta and structurally characterized through spectroscopic analysis. Additionally, the antifungal activity of these compounds against six plant-pathogenic fungal species was evaluated: Phytophthora nicotianae, Fusarium oxysporum, Alternaria alternata, Gloeosporium fructigenum Berk, Colletotrichum fructicola, and Botrytis cinerea. The results showed that the six compounds exhibited varying degrees of inhibitory effects on the six plant pathogens. Compound 1 showed the strongest antifungal effect in a dose-dependent way, with half-maximal effective concentration (EC50) values of 12.56, 51.29, and 47.86 μg/mL against P. nicotianae, F. oxysporum, and G. fructigenum Berk, respectively. Compound 3 and compound 6 also showed notable inhibitory effects against F. oxysporum and P. nicotianae at 100 μg/mL, with inhibition rates of 58.82% and 73.92%, respectively. The minimum inhibitory concentrations (MICs) of compound 1 against P. nicotianae and F. oxysporum were 200 and 400 μg/mL, respectively. Mechanistic analysis revealed that compound 1 induced pronounced ultrastructural deformations in P. nicotianae and F. oxysporum, compromising membrane integrity and elevating permeability in both pathogens. Notably, the three bioactive compounds exhibited favorable ADMET (absorption, distribution, metabolism, excretion, and toxicity) profiles, demonstrating promising candidacy as novel herbicidal agents. These findings underscore their potential to advance phytogenic fungicide discovery.